2010
DOI: 10.1183/09031936.00021810
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and fetal outcomes of symptoms of sleep-disordered breathing

Abstract: The physiological changes of pregnancy may predispose females to develop sleepdisordered breathing (SDB) or protect against it. Studies evaluating outcomes of SDB symptoms in pregnancy are scarce. The goal of this study was to evaluate the prevalence of SDB symptoms in pregnancy and their relationship with pregnancy and neonatal outcomes.A cross-sectional survey of randomly selected immediate postpartum females was performed using the multivariable apnoea prediction index. Record review, including demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
233
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(241 citation statements)
references
References 47 publications
5
233
2
1
Order By: Relevance
“…Previously, the same authors found that snoring, gasping, and apneas, all three symptoms of SRBD, were associated with higher mean ESS scores [7]. Furthermore, they found that these symptoms are common in pregnancy and associated with a higher likelihood of gestational hypertensive disorders, gestational diabetes, and unplanned caesarean deliveries [8]. The question, therefore, that arises is whether EDS assessed by ESS increases the risk of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…Previously, the same authors found that snoring, gasping, and apneas, all three symptoms of SRBD, were associated with higher mean ESS scores [7]. Furthermore, they found that these symptoms are common in pregnancy and associated with a higher likelihood of gestational hypertensive disorders, gestational diabetes, and unplanned caesarean deliveries [8]. The question, therefore, that arises is whether EDS assessed by ESS increases the risk of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…In addition, higher rates of unplanned Caesarean deliveries were found to be associated with both loud snoring [Bourjeily et al 2011] and OSA [Louis et al 2010]. Associations of snoring with critical fetal outcomes have also been shown including growth restriction in some studies [Franklin et al 2000;Micheli et al 2011 ] but not others [Bourjeily et al 2010;Loube et al 1996;Tauman et al 2011b]; preterm birth [Bourjeily et al 2010] and induced preterm birth [Louis et al 2010] were found in snorers and patients with OSA, respectively. This outcome may have been mediated by preeclampsia.…”
Section: Discussionmentioning
confidence: 97%
“…Snoring in pregnancy has been associated with key adverse pregnancy outcomes such as gestational hypertensive disorders [Bourjeily et al 2010;Calaora-Tournadre et al 2006;Franklin et al 2000;Perez-Chada et al 2007;Ursavas et al 2008] (OR 1.8-2.3 in most studies) [Bourjeily et al 2011] and gestational diabetes (aOR 2.1, 95% CI 1.3-3.4) [Bourjeily et al 2011;Facco et al 2010]. In addition, higher rates of unplanned Caesarean deliveries were found to be associated with both loud snoring [Bourjeily et al 2011] and OSA [Louis et al 2010].…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent data from a large pregnancy cohort showed that having OSA increases the risk of low birth weight, preterm birth, Cesarean section and preeclampsia. The two articles by Ebert et al 12 and Okun et al 13 in this issue of Journal of Clinical Sleep Medicine (JCSM) address the need to scientifi cally unravel this sleeping in pregnancy paradox.…”
mentioning
confidence: 99%
“…1 Meanwhile, there is growing evidence linking sleep disturbances with adverse pregnancy outcomes. [2][3][4] The message is clear: good sleep is important for a healthy pregnancy.…”
mentioning
confidence: 99%